Effect of post-harvest management on seed production of creeping red fescue, tall fescue, and Kentucky bluegrass in the Peace River region of north-western Canada - Fairey, N. A.; Lefkovitch, L. P. (Canadian Journal of Plant Science, 2001)
A field study in the Peace River region of northwestern Canada evaluated five post-harvest management (PHM) treatments on the seed yield and quality of four grasses, viz. Boreal creeping red fescue (Festuca rubra L. var. rubra), Safari and Tomahawk tall fescue (F. arundinacea Schreber), and Midnight Kentucky bluegrass (Poa pratensis L.). The PHM treatments were: straw removal after seed harvest plus trimming prior to winter; a single propane burn; a double propane burn; power cultivation; and diuron applied in spring. The study was conducted for 3 consecutive harvest years. The grass × harvest year × PHM interaction was not statistically significant (P ≤ 0.05) for any of 10 characteristics, viz. panicle density, time of seed maturity, seed yield (per unit land area and per individual panicle), whole-plant yield, harvest index, seed dockage, 1000-seed weight, specific seed weight, and germination capacity. The grass × harvest year interaction was statistically significant (P ≤ 0.05) for each of the 10 characteristics, primarily because of the differential response of the bluegrass as compared to the fescue grasses. The grass × PHM interaction was statistically significant (P ≤ 0.05) for seed yield of individual panicles, harvest index, seed dockage and 1000-seed weight. The PHM × harvest year interaction was statistically significant (P ≤ 0.05) for specific seed weight only. The main effect of PHM was statistically significant (P ≤ 0.05) for specific seed weight and germination capacity only. The average annual seed yield of the two tall fescue cultivars (1002 and 1171 kg ha –1 for Safari and Tomahawk) was approximately twice that of Boreal creeping red fescue (554 kg ha –1 ) and four times that of Midnight Kentucky bluegrass (284 kg ha –1 ). At this northerly latitude (55°N), the effects of any PHM treatment on the seed productivity of these grasses may be limited by the short period of environmental conditions between seed harvest and the onset of winter that are conducive to vegetative and reproductive tiller ...